Factors Influencing the E-Shoppers Perception towards E-Shopping (A Study with Special Reference to Wardha City) - Dr. Ramprakash O. Panchariya (International Journal of Engineering and Management Research, 2020)
Purpose: The study focuses on identifying and exploring the various factors influencing the e-shoppers perception towards e-shopping. Design / methodology / approach: A research model is developed based on the literature. For the purpose of study data collected from 100 e-shoppers belonged to Wardha City of Maharashtra. By using in structured questionnaire, descriptive statistical measure like mean has been used for analyzing the data. Findings: The results reveal that the seven key factors like convenience, time saving, home delivery, price advantage, more choice, reliability and security significantly influenced the e-shoppers perception on e-shopping. Contribution of the study: The result of this study provides a valuable reference to the e-marketers to understand the factors influencing e-shoppers perception. They can further sharpen their marketing strategies to attract and retain their customers.